A case control study on Infant Massage And Breastfeeding Outcome Among Mothers - Chan, Kim Geok; Pawi, Saloma; Lee, Shalin Wan Fei; Arabi, Zurraini; Hazmi, Helmy; Ooi, Chor Yau; Hii, Emily (2019)
Aims / Background: The practice of infant massage has been reported to provide benefits of improved mother-infant interaction and breastfeeding outcome. This study aims to examine the influence of infant massage on breastfeeding outcome.